Formation mechanism of contributors’ self-identity based on social identity in online knowledge communities - Gu, Tongfei; Cheng, Zhichao; Zhang, Zeqian; Li, Cui; Ni, Yuan; Wang, Xiaokang (Frontiers in Psychology, 2022)
Introduction Contributors’ self-identity is a critical element in the sustainable development of online knowledge communities (OKCs). However, research concerning the formation mechanism of contributors’ self-identity remains scarce. This research posits information support, novel posting and sense of self-worth as mediating variables between social identity and self-identity to construct a path model, aiming to explore the way in which self-identity is formed on the basis of social identity in OKCs. Methods To examine this mode, an online survey was administered to many different OKCs, and 515 usable questionnaire responses were collected. Structural equation modeling was then employed to examine the model. Results The R2 value of self-identity was 0.627, thus indicating that the model was able to explain 62.7% of the variance in self-identity. We find that self-identity emerges through the mediating effects of information support, novel posting and sense of self-worth. In addition, social identity can elicit novel posting and information support, which are all beneficial for enhancing the dynamics of OKCs and further generate sense of self-worth. We also observe that although social identity and individualized behavior (novel posting) are generally incompatible, they can be compatible in the context of OKCs. Discussion Self-identity as a contributor can be formed on the basis of social identity via the social path and the psychological path in OKCs, while the two paths for fostering self-identity are not independent of each other, and there is also a very strong link between behavioral and psychological mechanisms.